Amylose‐Coated Biohybrid Microgels by Phosphorylase‐Catalyzed Grafting‐From Polymerization. Issue 16 (4th June 2019) - Gau, Elisabeth; Flecken, Franziska; Belthle, Thomke; Ambarwati, Masyitha; Loos, Katja; Pich, Andrij
Abstract: Herein, the synthesis of amylose‐coated, temperature‐responsive poly( N ‐vinylcaprolactam) (VCL)‐based copolymer microgels by enzyme‐catalyzed grafting‐from polymerization with phosphorylase b from rabbit muscle is reported. The phosphorylase is able to recognize the oligosaccharide maltoheptaose as primer and attach glucose units from the monomer glucose‐1‐phosphate to it, thereby forming amylose chains while releasing inorganic phosphate. Therefore, to enable the phosphorylase‐catalyzed grafting‐from polymerization of glucose‐1‐phosphate from the PVCL‐based microgels, the maltoheptaose primer is covalently attached to the microgel in the first synthesis step. This is realized by adding N ‐(2‐aminoethyl)methacrylamide (AEMAA) as a comonomer to the PVCL microgel to integrate primary amino groups and subsequent coupling of maltoheptaonolactone. Both the PVCL/AEMAA microgel as well as the obtained microgel–maltoheptaose construct are characterized in detail by dynamic light scattering, electrophoretic mobility measurements, IR spectroscopy, and atomic force microscopy. From the microgel–maltoheptaose construct, the grafting‐from polymerization of glucose‐1‐phosphate is performed by the addition of phosphorylase b. Atomic force microscopy images clearly demonstrate the formation of an amylose shell around the microgels. The developed amylose‐coated microgels open up promising application possibilities, for example, as colloidal scavengers, since amylose helices can serve as host molecules for inclusion of hydrophobic guest molecules. Abstract : Amylose‐coated, temperature‐responsive poly( N ‐vinylcaprolactam) (PVCL)‐based microgels are synthesized by enzyme‐catalyzed grafting‐from polymerization with phosphorylase b from rabbit muscle. Maltoheptaose needed as polymerization primer is covalently attached to PVCL / AEMAA (N ‐(2‐aminoethyl) methacrylamide) microgels. From this construct, the grafting‐from polymerization of glucose‐1‐phosphate by phosphorylase b is performed, leading to the formation of amylose‐coated microgels.